2017
DOI: 10.1007/s12178-017-9401-z
|View full text |Cite
|
Sign up to set email alerts
|

Interspinous implants: are the new implants better than the last generation? A review

Abstract: Purpose of review Interspinous process devices (IPDs) are used in the surgical treatment of lumbar spinal stenosis. The purpose of this review is to compare the first generation with the next-generation devices in terms of complications, device failure, reoperation rates, symptom relief, and outcome. Recent findings Thirty-seven studies were included from 2011 to 2016. Device failure occurred at a mean of 3.7%, with a lower tendency to happen with next-generation IPDs. Reoperations occurred at a lower rate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Likely also postoperatively, alMRI provides a more realistic image of the spine morphology during spinal loading, compared to conventional MRI. Hence, the insufficient radiological effects of the IPD in the current study provide a reasonable patho-anatomical explanation to reported clinical treatment failure and high reoperation rates [8][9][10][11].…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Likely also postoperatively, alMRI provides a more realistic image of the spine morphology during spinal loading, compared to conventional MRI. Hence, the insufficient radiological effects of the IPD in the current study provide a reasonable patho-anatomical explanation to reported clinical treatment failure and high reoperation rates [8][9][10][11].…”
Section: Discussionmentioning
confidence: 61%
“…Contrarily, the ODS group displayed a DSCSA increase in changing from an absolute stenosis preoperatively to close to what is considered normal DSCSA postoperatively ( Table 2). The failure of the IPD to show radiological improvement postoperatively in alMRI might, at least to some extent, explain the general lack of long-term functionality and high reported reoperation rates among LSS patients treated with IPD [8][9][10][11]23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations